Austrumbaltijas eksperts Karls Reinholds Kupfers - Kuzņecova, Kristīne (My University, 2022)
Raksts par vācbaltu botāniķa Karla Reinholda Kupfera (1872-1935) dzīvi, Austrumbaltijas pētījumiem un citiem zinātniskajiem sasniegumiem.

An article about the life of the German-Baltic botanist Karl Reinhold Kupffer (1872-1935), his research of the Eastern Baltic region and other scientific achievements.
Eastern Baltics expert Karl Reinhold Kupffer
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Karls Reinholds Kupfers; botānika; Austrumbaltija